Komposisi Proksimat dari Gracilia Sp, Sargassum Sp, dan Ulva Lactuca di Pantai Sayang Heulang, Garut Selatan, Jawa Barat, Indonesia - Rusli, Handajaya; Lestari, Sri Dewi; Iqbal, Muhammad; Rusnadi, Rusnadi (Jurnal Kartika Kimia, 2023)
Carbohydrate protein, fat, and minerals are the main ingredients of seaweed besides water. These main contents can vary depending on environmental conditions and the type of seaweed. Gracilaria sp, Sargassum sp, and Ulva lactuca grow widely and have been used on Sayang Heulang beach, South Garut, West Java, Indonesia. Unfortunately, no information was found for its main content that can indicate the seaweed quality. This research aims to conduct a proximate analysis of the three seaweeds, representing brown seaweed, red seaweed, and green seaweed, respectively. Carbohydrate total analysis was done using Luff Schoorl method and gave 11.2 %w/w, 25.3 %w/w, and 20.4 %w/w for Gracilaria sp, Sargassum sp, and U. lactuca, respectively. Determination of total protein using the Kjeldahl-Nessler method gives 6.5 %w/w for Gracilaria sp, 7.8 %w/w for Sargassum sp, and 8.7 %w/w for U. lactuca. The methods for fat analysis are Soxhlet extraction, which gives 0.3 %w/w for Gracilaria sp, 1.6 %w/w for Sargassum sp, and 1.1 %w/w for U.lactuca. The study also showed Gracilaria sp, Sargassum sp, and U. lactuca contain 26.9 %w/w, 23.6 %w/w, and 32.5 %w/w mineral content, respectively. These results indicate that different types of seaweed provide different chemical compositions.